Cerebral oxygenation and hyperthermia - Bain, Anthony R.; Morrison, Shawnda A.; Ainslie, Philip N. (Frontiers in Physiology, 2014)
Hyperthermia is associated with marked reductions in cerebral blood flow (CBF). Increased distribution of cardiac output to the periphery, increases in alveolar ventilation and resultant hypocapnia each contribute to the fall in CBF during passive hyperthermia; however, their relative contribution remains a point of contention, and probably depends on the experimental condition (e.g. posture and degree of hyperthermia). The hyperthermia-induced hyperventilatory response reduces arterial CO2 pressure (PaCO2) causing cerebral vasoconstriction and subsequent reductions in flow. During supine passive hyperthermia, the majority of recent data indicate that reductions in PaCO2 may be the primary, if not sole, culprit for reduced CBF. On the other hand, during more dynamic conditions (e.g. hemorrhage or orthostatic challenges), an inability to appropriately decrease peripheral vascular conductance presents a condition whereby adequate cerebral perfusion pressure may be compromised secondary to reductions in systemic blood pressure. Although studies have reported maintenance of pre-frontal cortex oxygenation (assessed by near-infrared spectroscopy) during exercise and severe heat stress, the influence of cutaneous blood flow is known to contaminate this measure. This review discusses the governing mechanisms associated with changes in CBF and oxygenation during moderate to severe (i.e. 1.0°C to 2.0°C increase in body core temperature) levels of hyperthermia. Future research directions are provided.